Distinct Bile Acid Signature in Parkinson's Disease With Mild Cognitive Impairment - Nie, Kun; Li, Yanyi; Zhang, Jiahui; Gao, Yuyuan; Qiu, Yihui; Gan, Rong; Zhang, Yuhu; Wang, Lijuan (Frontiers in Neurology, 2022)
Backgrounds: Bile acid (BA) plays a crucial role in various neurodegenerative diseases, including Parkinson's Disease (PD). However, no clinical evidence supports BA's potential role in PD patients with mild cognitive impairment (PD-MCI). Objectives: This study aimed at investigating the differential BA profile between patients with PD-MCI and those with normal cognitive function (PD-NC). Methods: Ultra-high performance liquid chromatography-MS/MS was applied for BA quantitation. After between-group differences of BA profile were addressed, orthogonal projections to latent structures - discriminant analysis (OPLS-DA) and area under the receiver-operating-characteristic curve (AUC-ROC) were implemented for further verification. Results: Lower levels of Chenodeoxycholic acid (CDCA), Cholic Acid (CA), and Ursodeoxycholic Acid (UDCA) were significantly associated with PD-MCI (p＜0.01 for both; VIP≈2.67, 1.66, and 1.26, respectively). AUC-ROC were 78.1%, 74.2% and 74.5% for CDCA, CA and UDCA, respectively. Conclusion: CA, CDCA, and UDCA might be distinct BA signatures for PD-MCI patients.